PENGETAHUAN DAN PRAKTIK TENAGA PENCUCI ALAT SAJI SERTA IDENTIFIKASI KEBERADAAN BAKTERI Escherichia coliPADA PERALATAN MAKAN DI RUMAH SAKIT UMUM DAERAH (RSUD) K.R.M.T WONGSONEGORO SEMARANG - Utamia Trisnajati; Arintina Rahayuni; Astidio Noviardhi; Susi Tursilowati (Poltekkes Kemenkes Semarang, 2018)
Background: Cleanliness of food equipments are contributing to foodborne disease. Regulation of the Minister of Health of the Republic of Indonesia states that for the requirements of food equipment should not contain bacteria more than 100 colonies/cm2 and contains no bacteria Escherichia coli. Knowledge of food sanitation will affect the practice of food handler staff who are still not appropriate.Objective:To describe the knowledge and practice of washer staff and identification of Escherichia coli bacteria in eating utensil used in District General Hospital (RSUD) K.R.M.T Wongsonegoro Semarang.Method:This research is descriptive analysis, with observational study design. Sample of food equipment that is plate, glass, stainless plate, and spoon taken 32 samples with the repetition of the swabtest was done 2 repetitions.Laboratory test using swabtest test and MPN Escherichia coli in water. Univariate analysis is used to describe variable of washer staff knowledge, washer staff practice, and result of Escherichia coli identification. The relationship of knowledge and practice of washer staff using bivariate analysis.Results: Good knowledgeof washer staff are 56,3% and less knowledge are 43,7%. Practice of washer staff with good practice category are 62,5% and less category practice there are 37,5%. The results of the bacteriological identification of Escherichia coli in 32 samples of food equipment showed negative results and qualify Regulation Minister of Health Republic Indonsia No.715/Menkes/SK/V/2003,not containing the bacteria Escherichia coli. Analysis of Chi Square test data showed no significant relationship (p 0,05).Conclusion: The identification results of Escherichia Coli are negative on cutlery and it is accordance with the requirements of the Regulation Minister of Health Republic Indonesia No. 715/Menkes/SK/V/2003. There is no relationship between knowledge with the practice of staff washer.